Effect of Planting Density on the Agronomic Performance and Fruit Quality of Three Pineapple Cultivars (Ananas comosus L. Merr.) - Juan C. Neri; Jegnes Benjamín Meléndez Mori; Nuri Carito Vilca Valqui; Eyner Huaman Huaman; Roicer Collazos Silva; Manuel Oliva (International Journal of Agronomy)
Pineapple is a crop of great importance for the economic stability of a large number of Peruvians; however, in areas experiencing low degrees of technological intervention, farmers generally adopt low planting densities. The objective of this study was to determine the effect of three plantation densities (35700, 47600, and 55500 plants ha−1) on the agronomic performance and fruit quality of three pineapple cultivars (“Golden,” “Smooth Cayenne,” and “Santa Rosa” ecotype). The experiment was performed under a randomized complete block design (RCBD) in a factorial arrangement, and the data were subjected to analysis of variance and the Tukey test (p<0.05). The results show significant differences in terms of plant height and D-leaf length, with “Golden” being the cultivar that achieved the best performance at the three planting densities. The diameter (11.77–13.29 cm) and weight of the fruit without a crown (1.48–1.85 kg) were not affected by the treatments; in contrast, the length and weight of the fruit with a crown did exhibit significant variations, highlighting the “Smooth Cayenne” cultivar and “Santa Rosa” ecotype at a density of 55500 plants ha−1, respectively. The highest estimated yield (>100 t ha−1) for the three pineapple cultivars was recorded at a density of 55500 plants ha−1. The content of total soluble solids was higher in the “Golden” cultivar, but in general, all the fruits exceeded the established standards. Based on the results, it is recommended that farmers in the area and those with similar conditions establish a planting density of 55500 plants ha−1 because it improves the yield without damaging the quality of the fruit of the pineapple cultivars evaluated.